Microeconomics - Parkin, Michael 1939- (Pearson, 2008)
Macroeconomics, eighth edition, retains all of the improvements achieved in its pre-decessor with it thorough and detailed presentation of modern economics, emphasis on real-world examples and critical thinking skills, diagrams renowned for pedagogy and precision, and path-breaking technology